Sumpong spirit beliefs, murder, and religious change among eighteenth-century Aeta and Ilongot in Eastern Centeral Luzon - Dizon, Mark (Quezon City Ateneo de Manila University, 2015)
"In common usage and in psychology sumpong is considered a deviant and irrational behavior. This article makes sense of sumpong by putting it in the historical context of animism, specifically that of the eighteenth-century Aeta and Ilongot of eastern Central Luzon. As a form of perception, feeling and action, sumpong was temporally flat since past, present, and future did not succeed one another in linear fashion. Based on historical dictionaries and usage, this article explores the role of sumpong as an affective and culturally intelligible way of understanding and acting in the animist world as seen in cases of murder and religious change."
Keywords: Christianity; Animism; Headhunting